A perovskite microcrystalline film and its preparation method and application
The preparation of perovskite microcrystalline films using pre-synthesized micro single crystals and controlled processing methods addresses stability and absorption issues, resulting in high-efficiency, stable films suitable for large-area perovskite solar cells.
Patent Information
- Application Number
- CN202410427738.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-04-10
AI Technical Summary
Existing perovskite solar cell technologies face issues with high defect state density, poor stability under wet and hot conditions, and limited suitability for large-area thin film preparation, leading to inefficient absorption of visible light and reduced power conversion efficiency.
A method involving the use of pre-synthesized perovskite micro single crystals, anti-solvent, and dispersant, followed by ball milling, spraying, and thermal annealing to form a perovskite microcrystalline film, which includes solvent post-treatment to enhance film quality and stability.
The method produces high-quality, stable perovskite microcrystalline films with improved air, thermal, and moisture stability, wider absorption range, and enhanced power conversion efficiency, suitable for large-area applications.
Smart Images

Figure CN118317666B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic device preparation, and in particular to a perovskite microcrystalline film and a preparation method and application thereof. Background Art
[0002] Organic-inorganic hybrid perovskite has been widely used and studied due to its excellent optoelectronic properties, including long exciton and charge diffusion lengths, high extinction coefficients, and low-temperature processability. It is a good material for the light-absorbing layer of solar cells (PSCs). Previous studies have focused on the preparation of light-absorbing layer films using in-situ crystallization techniques using a one-step or two-step method. Currently, the power conversion efficiency (PCE) of perovskite solar cells with light-absorbing layers prepared using this in-situ crystallization method has exceeded 26%. However, the perovskite crystal films obtained by these methods have a high defect state density of 1015-1019cm -3 The stability is poor. Under wet and hot conditions, a certain degree of decomposition occurs after 48 hours. Scientists have adopted various defect passivation and additive engineering, but they cannot effectively improve its long-term stability, which has become a major scientific and technological issue in this field. At the same time, the absorption spectrum of the in-situ polycrystalline thin film shows a significant downward trend after 500nm, which is not conducive to the absorption of the entire visible light band and the utilization of spectral energy by solar cells. Moreover, the process of preparing the active layer of solar cells by in-situ spin coating crystallization is not suitable for the preparation of large-area thin films. Recently, methods such as blade coating and dual-source co-evaporation have also been used to prepare large-area thin films, but they are still limited to in-situ preparation, which cannot effectively improve the long-term stability of device operation, nor can it simplify the process flow. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a perovskite microcrystalline film and a preparation method and application thereof. The method provided by the present invention can stably prepare a perovskite film with high flatness and high stability.
[0004] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a perovskite microcrystalline film:
[0005] (1) mixing the perovskite micro single crystal, the anti-solvent and the dispersant and then ball milling to obtain a dispersed system;
[0006] (2) spraying and thermally annealing the obtained dispersion system on a substrate material in sequence to obtain the perovskite microcrystalline film;
[0007] The general structure formula of the perovskite micro single crystal is ABX3, wherein A=MA, FA, Cs and a mixture of two or three thereof, B=Pb, and X=I, Br or Cl.
[0008] Preferably, the mass volume ratio of the perovskite micro single crystal, anti-solvent and dispersant is (0.15-0.20) g: (0.5-1.5) mL: (0.015-0.02) g.
[0009] Preferably, the anti-solvent is anisole, ethyl acetate or n-hexane.
[0010] Preferably, the dispersant is terpineol.
[0011] Preferably, the spraying parameters are: spraying distance is 8-15 cm, spraying carrier gas pressure is 40 Psi, and spraying interval is 10 s.
[0012] Preferably, after spraying the dispersed system on the substrate material, the method further includes solvent post-treatment.
[0013] Further preferably, the solvent post-treatment is: quickly transferring the sprayed substrate material to a hot stage and spraying it with γ-valerolactone.
[0014] Preferably, the thermal annealing treatment is performed at a temperature of 100° C. and for a time of 1 hour.
[0015] The present invention also provides a perovskite microcrystalline film obtained by the preparation method described in the above technical solution.
[0016] The present invention also provides a solar cell, wherein the light absorbing layer material comprises the perovskite microcrystalline film described in the above technical solution.
[0017] Beneficial technical effects:
[0018] 1. This process selects pre-synthesized ABX3 (A = MA, FA, Cs and a mixture of two or three components, B = Pb, X = I, Br, Cl) micro single crystals for non-in-situ thin film preparation. The preparation process is simple and the prepared thin film has good photoelectric properties and is suitable for large-area, commercial preparation.
[0019] 2. The present invention uses a spraying method in an air environment, adopts pre-synthesized micro single crystals as raw materials, and non-in-situ and rapidly prepares high-quality micro single crystal films. The production process is simple and more suitable for industrial production.
[0020] 3. Compared with polycrystalline, micro single crystal has narrower band gap. At the same time, micro single crystal has better air stability, thermal stability and moisture stability than thin film. Micro single crystal has wider absorption range than polycrystalline, and achieves full absorption in the visible light range. The micro single crystal film prepared by the present invention can well retain the above properties, which makes the non-in-situ preparation of perovskite micro single crystal film a strong alternative for large-area, commercial preparation of perovskite optoelectronic device functional layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 The SEM images of the films obtained in Example 1 and Comparative Example 1, wherein (a) is Comparative Example 1, and (b) is Example 1;
[0023] Figure 2 is the XRD pattern of the film obtained in Example 1;
[0024] Figure 3 The UV-visible absorption spectrum and fluorescence spectrum of the film obtained in Example 1;
[0025] Figure 4 This is a comparison chart of the efficiency of the devices obtained after preparing solar cell devices using the thin films obtained in Example 1 (after solvent post-treatment) and Comparative Example 1 (without solvent post-treatment). DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] The present invention provides a method for preparing a perovskite microcrystalline film:
[0032] (1) mixing the perovskite micro single crystal, the anti-solvent and the dispersant and then ball milling to obtain a dispersed system;
[0033] (2) spraying and thermally annealing the obtained dispersion system on a substrate material in sequence to obtain the perovskite microcrystalline film;
[0034] The general structure formula of the perovskite micro single crystal is ABX3, wherein A=MA, FA, Cs and a mixture of two or three thereof, B=Pb, and X=I, Br or Cl.
[0035] In the present invention, the perovskite microcrystals should be regular, high in crystallinity, and low in defect state density. The quality of the micro single crystals will affect the device efficiency to a certain extent. The present invention has no special restrictions on the source of the perovskite microcrystals, and can be obtained by a preparation method well known to those skilled in the art, or obtained through commercial channels, as long as the perovskite microcrystals have a regular structure, high in crystallinity, and low in defect state density.
[0036] The present invention uses perovskite microcrystals obtained by strictly adhering to the stoichiometric ratio, and the solvent used in the prepared dispersion system is an anti-solvent. Compared with the in-situ preparation of the functional layer, this process can not only retain the advantages of high stability and wide absorption of the microcrystals, but also is more conducive to application in industrial production.
[0037] The present application adopts a non-in-situ film-forming method of spraying, controls the film-forming conditions, and can stably prepare a perovskite film with high flatness and high stability. The present invention also systematically characterizes its environmental stability and spectral absorption characteristics. The results show that the film obtained by the method of the present application has excellent stability and retains the strong absorption characteristics of the microcrystals in the range of 300-850nm. It is a desirable non-in-situ method for preparing the light absorption layer of the perovskite solar cell, which may be able to solve the problem of the operating stability of the device and promote the practical application of perovskite solar cells.
[0038] The present invention first mixes perovskite micro single crystals, anti-solvents and dispersants and then performs ball milling to obtain a dispersed system.
[0039] In some embodiments, the mass volume ratio of the perovskite microcrystals, anti-solvent, and dispersant is preferably (0.15-0.20) g: (0.5-1.5) mL: (0.015-0.02) g, and more preferably 0.186 g: 1 mL: 0.0186 g. In the present invention, if the mass of the microcrystals is small, the dispersion will be too thin, and the obtained film will be uneven; if the mass of the microcrystals is large, the dispersion will be too thick, clogging the gun tip, and it will be difficult to form a film by spraying. If there is too much dispersant, the composition of the dispersion will change, and the dispersant is mostly a high-boiling point substance, which is difficult to remove in the subsequent process; if there is too little dispersant, it is difficult to form a relatively uniform and stable dispersion system during the ball milling process. Therefore, the preferred mass volume ratio of the present invention is (0.15-0.20) g: (0.5-1.5) mL: (0.015-0.02) g.
[0040] In some embodiments, the particle size of the perovskite is preferably 500-1000 nm. In the present invention, the perovskite crystals with too small particle size cannot ensure uniformity, and the obtained film has poor flatness, while the particle size is too large and will clog the gun tip. Therefore, the preferred particle size range of the present invention is 500-1000 nm.
[0041] In some embodiments, the anti-solvent is preferably anisole, ethyl acetate or n-hexane, more preferably anisole. Commonly used anti-solvents include chlorobenzene, dichloromethane, acetonitrile, etc., but chlorobenzene has a higher toxicity, and dichloromethane has a low boiling point, is easily volatilized during ball milling, and is difficult to control the dispersion concentration. Therefore, the preferred anti-solvent of the present invention is anisole.
[0042] In some embodiments, the dispersant is preferably pineol. In the present invention, alcohol dispersants (such as methanol, ethanol, etc.) may dissolve micro single crystals to a certain extent and are not suitable for the preparation of the method of the present invention, while other inorganic dispersants (such as aluminum oxide, silicon dioxide, etc.) are difficult to remove during the subsequent annealing process, and inclusions in the film will inhibit the transport of perovskite carriers. Therefore, the preferred dispersant of the present invention is pineol.
[0043] The present invention does not impose any particular limitation on the mixing method of the perovskite microcrystals, the antisolvent, and the dispersant. Any mixing method familiar to those skilled in the art may be used, preferably ultrasonic mixing, and the ultrasonic time is preferably 1 hour.
[0044] The present invention does not specifically limit the ball milling method, and a ball milling method well known to those skilled in the art can be selected. The ball milling time is preferably 10-12 hours, more preferably 12 hours. Too short a ball milling time makes it difficult to form a uniform dispersion system, while too long a ball milling time will lead to volatilization of the dispersant and changes in the crystal morphology. Therefore, the preferred ball milling time of the present invention is 10-12 hours.
[0045] After obtaining the dispersed system, the present invention sequentially sprays and thermally anneals the dispersed system on the substrate material to obtain the perovskite microcrystalline film.
[0046] In some embodiments, the spraying parameters are: spraying distance is 8-15 cm, spraying carrier gas pressure is 40 Psi, and spraying interval is 10 s.
[0047] The present invention can control the thickness of the obtained film by controlling the number of spraying times.
[0048] In some embodiments, after the dispersion system is sprayed on the substrate material, a solvent post-treatment is further included; the solvent post-treatment is: the sprayed substrate material is quickly transferred to a hot stage and sprayed with γ-valerolactone; the temperature of the hot stage is 80°C; the conditions for spraying γ-valerolactone are the same as the above-mentioned spraying parameters; the number of spraying of γ-valerolactone is preferably 3-5 times, more preferably 3 times. In the present invention, γ-valerolactone is a good solvent for perovskite, which can dissolve small crystals and promote the secondary growth of large crystals, playing a role of "filling the gap". Other good solvents such as commonly used DMF, DMSO, etc. have lower boiling points than γ-valerolactone, resulting in a shorter residence time, and the recrystallization process cannot be completed well, and the resulting film is not as smooth as that treated with γ-valerolactone.
[0049] In the present invention, the subsequent solvent post-treatment operation can promote the perovskite film to further dissolve and recrystallize to fill the gaps, thereby promoting further improvement of the density and flatness of the film and improving the efficiency of the device. It is difficult to form a dense film without the solvent post-treatment step.
[0050] In some embodiments, the thermal annealing treatment is performed at a temperature of 100° C. and for a time of 1 hour.
[0051] The present invention also provides a perovskite microcrystalline film obtained by the preparation method described in the above technical solution.
[0052] Taking MAPbI3 micro single crystal as an example, the preparation method of the perovskite microcrystalline film includes the following steps:
[0053] (1) Preparation of perovskite dispersion system: MAPbI3 micro single crystals and 1 ml of anisole and pinene alcohol were mixed by ultrasonication and ball milling to obtain a uniform and stable dispersion system;
[0054] (2) Preparation of perovskite layer: Add the perovskite dispersion system obtained by ball milling into the spray gun for spraying. The spraying distance is 8-15cm, the carrier gas pressure is 40Psi, and the spraying interval is 10s. The thickness of the obtained film can be controlled by controlling the number of spraying times;
[0055] (3) Solvent post-treatment: The substrate coated with the perovskite layer was quickly transferred to a hot plate at 80 °C and sprayed with γ-valerolactone under the same spraying conditions as in the preparation of the perovskite layer described above;
[0056] (4) Thermal annealing: The substrate after solvent post-treatment was transferred to a hot plate at 100° C. for thermal annealing for 1 h.
[0057] The present invention also provides a solar cell, wherein the light absorbing layer material comprises the perovskite microcrystalline film described in the above technical solution.
[0058] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0059] Unless otherwise specified, the raw materials used in the following examples can be obtained through commercial sources.
[0060] Example 1
[0061] Taking MAPbI3 micro single crystal as an example, the preparation method of the perovskite microcrystalline film includes the following steps:
[0062] (1) Preparation of perovskite dispersion system: 0.186 g (0.3 mmol) of MAPbI3 micro-single crystals, 1 ml of anisole, and 0.0186 g (10% of the mass of the micro-single crystals) of pinene alcohol were mixed by ultrasonication for 1 h and ball milled for 12 h to obtain a uniform and stable dispersion system;
[0063] (2) Preparation of perovskite layer: Add the perovskite dispersion system obtained by ball milling into the spray gun for spraying. The spraying distance is 8-15cm, the carrier gas pressure is 40Psi, and the spraying interval is 10s. The thickness of the obtained film can be controlled by controlling the number of spraying times;
[0064] (3) Solvent post-treatment: The substrate coated with the perovskite layer was quickly transferred to a hot plate at 80 °C and sprayed with γ-valerolactone for post-treatment, which was sprayed three times under the same spraying conditions;
[0065] (4) Thermal annealing: The substrate after solvent post-treatment was transferred to a hot plate at 100° C. for thermal annealing for 1 h.
[0066] Comparative Example 1
[0067] Same as Example 1, except that (3) solvent post-treatment step is omitted.
[0068] Scanning electron microscopy (SEM) was used to characterize the surface morphology of the prepared films. Figure 1As shown in (a), the film without solvent post-treatment (Comparative Example 1) clearly shows crystal boundaries, the crystals are not tightly packed, and the crystals are mostly hexahedral and regular in shape, but the crystal boundaries are obvious and the defect state density is high. Figure 1 (b), the film surface is flat, with fewer grain boundaries and a lower defect density. The film thickness after solvent treatment is about 1-5μm (1μm after 3 sprayings, gradually thickening with the increase in the number of sprayings, and about 5μm after 7 sprayings). It is known that the carrier diffusion length of MAPbI3 micro-single crystals is about 106μm, which is much higher than the film thickness. Therefore, carriers can be well transported in the prepared micro-single crystal film.
[0069] X-ray diffraction was used to characterize the prepared MAPbI3 micro single crystal film. Figure 2 As shown in the XRD diagram, it is clearly visible that the microcrystals have no peaks at 2θ angles of 10.9° (MAI characteristic peak) and 11.8° (PbI2 characteristic peak), and they are well matched with the standard MAPbI3 absorption peaks. The main peaks are located at about 14° and 28°, corresponding to the (002) and (110) crystal planes, respectively, indicating that it has a tetragonal structure. The double peaks at 28.5° corresponding to the (200) crystal plane also prove that it is a tetragonal phase. This shows that the prepared micro single crystal film retains the high crystallinity characteristics of the micro single crystals very well.
[0070] The obtained microcrystals were characterized by absorption, and their UV-visible absorption spectrum and fluorescence spectrum were as follows: Figure 3 As shown. Through the tangent and the vertical axis of the curve, it can be calculated that this microcrystalline powder is a direct bandgap semiconductor. The absorption spectrum shows that the ultraviolet absorption curves of the micro single crystal film and the single crystal are almost the same. The absorption band edge of the polycrystalline film is around 800nm, while the absorption band edge of the micro single crystal film and the single crystal is around 850nm, and the absorption peak of the polycrystalline film decreases significantly at 550nm. The micro single crystal film is similar to the single crystal, retaining the characteristics of the micro single crystal for the full band absorption of visible light, increasing the absorption and utilization of energy under the bandgap, thereby increasing the theoretical upper limit of the short-circuit current density (JSC) and power conversion efficiency (PCE) of the PSC.
[0071] The obtained film retains the high stability of the micro single crystal and can maintain its initial XRD, PL and UV absorption spectra when placed in an environment of 80°C (high temperature) and 80%-90% humidity (high humidity) for 500 hours and 100 hours respectively.
[0072] The micro single crystal thin film prepared in Example 1 and Comparative Example 1 was used to prepare a solar cell device, and a device structure of FTO / c-TiO2 / m-TiO2 / Perovskite / Spiro-OMeTAD / Au was used, such as Figure 4As shown, the device efficiency of the solvent-treated film increased from 1.11% to 10.79%.
[0073] In summary, the micro-single crystal film prepared in this application inherits the excellent optoelectronic properties of micro-single crystals, has a long carrier diffusion length (106.25 μm), a low defect state density (9.43*10 10 cm -3 ) characteristics, maintaining full absorption in the visible light range of 300-850nm, with room for further improving energy efficiency. In addition, the process flow is simplified, and high-stability perovskite microcrystal film formation can be used as a highly promising preparation technology for commercial preparation of functional layers of perovskite solar cells.
[0074] Example 2
[0075] The same as Example 1, except that 0.186g (0.3mmol) of MAPbI3 micro-single crystals, 1ml of anisole, and 0.0186g (10% of the mass of the micro-single crystals) of pinene alcohol are replaced with 0.15g of MAPbI3 micro-single crystals, 0.5ml of anisole, and 0.015g (10% of the mass of the micro-single crystals) of pinene alcohol.
[0076] The performance test of the perovskite microcrystalline film obtained in Example 2 was carried out, and the results were similar to those in Example 1. The film surface after solvent post-treatment was flat, with fewer grain boundaries, and the defect state density was also reduced. The film thickness was about 1-5 μm (the thickness was 1 μm after 3 sprayings, and gradually thickened with the increase in the number of sprayings, and the thickness was about 5 μm after 7 sprayings), and the obtained micro single crystal film well retained the characteristics of high crystallinity of micro single crystals; its absorption spectrum was similar to that of single crystals, retaining the characteristics of micro single crystals absorbing the entire visible light band, increasing the absorption and utilization of energy under the band gap, thereby increasing the short-circuit current density (JSC) and the theoretical upper limit of power conversion efficiency (PCE) of PSC; the obtained film well retained the characteristics of high stability of micro single crystals; after it was used to prepare solar devices, the device efficiency was significantly improved.
[0077] Example 3
[0078] The same as Example 1, except that 0.186g (0.3mmol) of MAPbI3 micro-single crystals, 1ml of anisole, and 0.0186g (10% of the mass of the micro-single crystals) of pine alcohol are replaced with: 0.20g of MAPbI3 micro-single crystals, 1.5ml of anisole, and 0.02g (10% of the mass of the micro-single crystals) of pine alcohol.
[0079] The performance test of the perovskite microcrystalline film obtained in Example 3 was carried out, and the results were similar to those in Example 1. The film surface after solvent post-treatment was flat, with fewer grain boundaries, and the defect state density was also reduced. The film thickness was about 1-5 μm (the thickness was 1 μm after 3 sprayings, and gradually thickened with the increase in the number of sprayings, and the thickness was about 5 μm after 7 sprayings), and the obtained micro single crystal film well retained the characteristics of high crystallinity of micro single crystals; its absorption spectrum was similar to that of single crystals, retaining the characteristics of micro single crystals absorbing the full band of visible light, increasing the absorption and utilization of energy under the band gap, thereby increasing the short-circuit current density (JSC) and the theoretical upper limit of power conversion efficiency (PCE) of PSC; the obtained film well retained the characteristics of high stability of micro single crystals; after it was used to prepare solar devices, the device efficiency was significantly improved.
[0080] Example 4
[0081] Same as Example 1, except that anisole is replaced by ethyl acetate.
[0082] The performance test of the perovskite microcrystalline film obtained in Example 4 was carried out, and the results were similar to those in Example 1. The film surface after solvent post-treatment was flat, with fewer grain boundaries, and the defect state density was also reduced. The film thickness was about 1-5 μm (the thickness was 1 μm after 3 sprayings, and gradually thickened with the increase in the number of sprayings, and the thickness was about 5 μm after 7 sprayings), and the obtained micro single crystal film well retained the characteristics of high crystallinity of micro single crystals; its absorption spectrum was similar to that of single crystals, retaining the characteristics of micro single crystals absorbing the full band of visible light, increasing the absorption and utilization of energy under the band gap, thereby increasing the short-circuit current density (JSC) and the theoretical upper limit of power conversion efficiency (PCE) of PSC; the obtained film well retained the characteristics of high stability of micro single crystals; after it was used to prepare solar devices, the device efficiency was significantly improved.
[0083] Example 5
[0084] Same as Example 1, except that anisole is replaced by n-hexane.
[0085] The performance test of the perovskite microcrystalline film obtained in Example 5 was carried out, and the results were similar to those in Example 1. The film surface after solvent post-treatment was flat, with fewer grain boundaries, and the defect state density was also reduced. The film thickness was about 1-5 μm (the thickness was 1 μm after 3 sprayings, and gradually thickened with the increase in the number of sprayings, and the thickness was about 5 μm after 7 sprayings), and the obtained micro single crystal film well retained the characteristics of high crystallinity of micro single crystals; its absorption spectrum was similar to that of single crystals, retaining the characteristics of micro single crystals absorbing the full band of visible light, increasing the absorption and utilization of energy under the band gap, thereby increasing the short-circuit current density (JSC) and the theoretical upper limit of power conversion efficiency (PCE) of PSC; the obtained film well retained the characteristics of high stability of micro single crystals; after it was used to prepare solar devices, the device efficiency was significantly improved.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a perovskite microcrystalline film, characterized in that: The perovskite micro single crystal, anti-solvent and dispersant are mixed and then ball-milled to obtain a dispersed system; The obtained dispersion system is sequentially sprayed and thermally annealed on a substrate material to obtain the perovskite microcrystalline film; The general structure formula of the perovskite micro single crystal is ABX3, wherein A=MA, FA, Cs and a mixture of two or three thereof, B=Pb, and X=I, Br or Cl; After spraying the dispersed system on the substrate material, the method further includes solvent post-treatment; The solvent post-treatment is: quickly transferring the sprayed substrate material to a hot stage and spraying it with γ-valerolactone.
2. The preparation method according to claim 1, characterized in that: The mass volume ratio of the perovskite micro single crystal, anti-solvent and dispersant is (0.15-0.20) g: (0.5-1.5) mL: (0.015-0.02) g.
3. The preparation method according to claim 1 or 2, characterized in that: The anti-solvent is anisole, ethyl acetate or n-hexane.
4. The preparation method according to claim 1 or 2, characterized in that: The dispersant is terpineol.
5. The preparation method according to claim 1, characterized in that: The spraying parameters are as follows: spraying distance is 8-15 cm, spraying carrier gas pressure is 40 Psi, and spraying interval is 10 s.
6. The preparation method according to claim 1, characterized in that: The temperature of the thermal annealing treatment is 100° C. and the time is 1 hour.
7. A perovskite microcrystalline film obtained by the preparation method according to any one of claims 1 to 6.
8. A solar cell, characterized in that: The light absorbing layer material comprises the perovskite microcrystalline thin film as claimed in claim 7.
Citation Information
Patent Citations
Method for improving crystallinity of perovskite
CN106128954A
Perovskite thin film post-treatment device, use method and application thereof
CN108987577A
Preparation method of perovskite microcrystalline film and solar cell device
CN112234144A
Direct-indirect hybrid perovskite X-ray detector and photoyield calculation method of scintillator thereof
CN113394344A
Perovskite precursor and preparation method thereof
CN116648447A
